Software engineering based fault tolerance model for information system in plants shopping center - Saja Nasir; Muayad Croock; Salih Al-Qaraawi (Institute of Advanced Engineering and Science, 2020)
The rapid development of mobile phone technologies in recent years promoted them for being used in various areas of life, such as commercial, health, transportation and tourism and other uses. In this paper, a software engineering based fault tolerance model is proposed to manage the expected faults in the adopted servers. The underlying QR based information system in plants shopping center employs different local serves allocated at local shops that are connected to the main server. In a fault case detection at any local server, the main server can cover the management of the system until the maintenance is completed. This is performed in efficient way as the main server keeps a copy of the information for all local branches. It is important to note that the self-checking process is adopted for fault detection. After completing the maintenance, a copy of the updated information is sent back to the investigated local server including all sales, etc. Moreover, the main and local servers contain information about all offer’s plants in different languages and in text and image form, customer's information and admin's information. The proposed system is tested in several cases to prove the efficiency and effectivity in retrieving and managing information and data as well as the fault tolerance administration.